FAIRNESS AS A SHIELD: ORGANISATIONAL JUSTICE, COMMITMENT AND EMOTIONAL EXHAUSTION AMONG MALAYSIAN UNIVERSITY ACADEMICS - Kuek, Thiam Yong; Chen, I-Chi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This conceptual study explores the relationship between organisational justice and emotional exhaustion among academics in Malaysian universities, drawing on the Job Demands–Resources (JD-R) theoretical model. It posits that organisational justice, encompassing fairness acts as a crucial job resource that can alleviate emotional exhaustion—a key dimension of burnout. Additionally, the research examines the moderating role of organisational commitment, proposing that highly committed academics may experience a stronger protective effect of organisational justice against emotional exhaustion. The study fills a gap in the literature by integrating organisational justice into the JD-R framework and highlighting its role in academic well-being. By emphasizing the importance of fair organisational practices, this research offers insights for higher education leaders to create supportive environments that reduce burnout. It underscores the value of fostering organisational commitment to mitigate emotional exhaustion and improve overall academic performance and well-being.